ANALISA TINGKAT KEBISINGAN DI KAWASAN PENDIDIKAN SMPN 59 JAKARTA - Hendri Noperi; Mega Reta Triyuniar (KOLONI, 2022)
School is a place where the teaching and learning process takes place. The Government of Indonesia has established the National Standard (SNI) for Education Areas. Optimal learning activities really need a conducive and calm environment because students need high concentration during the learning process. Schools that are close to the highway will greatly interfere with ongoing student activities. SMPN 59 Jakarta is one of the public junior high schools located in the center of Jakarta City and is located in a crowded area of population. Noise measurements were carried out for 2 days, active learning days and holidays. The results show that the noise level in SMPN 59 Jakarta is in the zone that is intended for the Education Area. Keywords: noise, sound, school, learning